Deep vein thrombosis prevention with triad of soluble aspirin, pneumatic compression device and early mobilization in surgically managed proximal femur fracture: an observational study - Deepak, Dilip Kumar; Singh, Anuj (International Journal of Research in Orthopaedics, 2021)
Background: To evaluate the effectiveness of regime of thromboprophylaxis including soluble aspirin, pneumatic compression devices and early mobilization in prevention of deep vein thrombosis (DVT) with patients of proximal femoral fracture managed by internal fixation. Methods: The study was an observational study conducted at tertiary care hospital of Indian armed forces with sample size of n= 50, diagnosed case of fracture proximal femur and managed operatively with soluble aspirin and pneumatic compression devices and early mobilization. Patients were observed and evaluated periodically for 12 weeks post discharge with colour doppler assessment. Results: The findings at end of 2 Week, n=1 (2%, p<0.003) had findings suggested of DVT and n=49 (98%) had no signs of DVT. Next periodic evaluation at 6 weeks and 12 weeks n=50 (100% p<0.001) was devoid of any doppler findings suggestive of DVT. Conclusions: The observational prospective study demonstrated the triad of soluble aspirin, pneumatic compression and early mobilization were efficacious in prevention of DVT in surgically managed cases of fracture proximal femur.